RE-LAYOUT TATA LETAK FASILITAS PRODUKSI IMITASI PVC DENGAN MENGGUNAKAN METODE SYSTEMATIC LAYOUT PLANNING DAN BLOCPLAN - Alfian Dwi Budianto; Atikha Sidhi Cahyana (Jurnal Ilmiah Dinamika Teknik, 2021)
Layout of production facilities at PT. XYZ has been identified as experiencing interference in its production flow. At the moment the condition of the production site in PT. XYZ is still inadequate in view of the laying of machines and workstations that look very far away. One example is in the department G (winder), because there is a matrial buildup that often occurs due to the lack of utilization of the area and the distance of material transfer is too long also the area to go to the department H (oven) with a long distance that is able to cause inefficiency and effective during the production process. The method used to plan and design the layout of production facilities in PT. XYZ is the Systematic Layout Planning (SLP) and Blocplan methods. This method was chosen because it corresponds to the characteristics of the company that requires adjustments in arranging facilities on the production floor. The result of SLP and Blocplan is the main basis for providing improvements to the layout of proposed improvements to pt. XYZ is able to optimize the production results more, by providing a good proposal of production area process flow with the process flow of the previous production area. The efficiency rate of the Blocplan Algorithm is 30%, and for efficiency to change between departmental distances in the initial layout and the proposed layout by 21%.